Biostimulants based nutrient management on growth and yield of spring maize (Zea mays) under legume based cropping sequence - PRAVEEN, B R; SINGH, MAGAN; BABU, R T CHETHAN; KUMAR, SANJEEV; NARAGUND, RUXANABI; SACHIN, K S; PYATI, PRASANNA S; KUMAR, RAKESH; TELI, KASHINATH GURUSIDDAPPA (The Indian Journal of Agricultural Sciences, 2024)
The study was carried out during 2020–21 and 2021–22 at ICAR-National Dairy Research Institute, Karnal, Haryana to evaluate biostimulants based nutrient management practices in spring maize (Zea mays L.) under legume based cropping sequence. Experiment was conducted in a randomized block design (RBD) with 9 treatments of biostimulant based nutrient management, viz. T1, Absolute control; T2, 100% RDF (recommended dose of fertilizer); T3, 75% RDF + Azotobacter; T4, 50% RDF + Azotobacter + PGPR (Plant growth promoting rhizobacteria); T5, 75% RDF + Azotobacter + PGPR; T6, 50% RDF + Azotobacter + PGPR + Humic acid (HA); T7, 75% RDF + Azotobacter + PGPR + HA; T8, 50% RDF + Azotobacter + PGPR + HA + Seaweed extract (SWE); and T9, 75% RDF + Azotobacter + PGPR + HA + SWE, replicated thrice. Results showed that the growth parameters, viz. plant height, leaf length, leaf width and number of leaves/plant had no significant response at 30 DAS (days after sowing) during both the studied year. However, at 60 DAS, these parameters were significantly higher in 100% RDF which was statistically on par with 75% RDF + Azotobacter + PGPR + Humic acid (HA) + Seaweed extract (SWE) and 75% RDF + Azotobacter + PGPR + HA. Whereas at harvest, growth attributes were significantly higher in 75% RDF + Azotobacter + PGPR + HA + SWE which was statistically on par with RDF + Azotobacter + PGPR + HA and 100% RDF. Similarly, grain (7.81 and 8.00 t/ha), stover (12.18 and 12.48 t/ha) and biological yield (22.47 and 22.92 t/ha) were significantly higher in 75% RDF + Azotobacter + PGPR + HA + SWE which was statistically on par to RDF + Azotobacter + PGPR + HA and 100% RDF during 2020–21 and 2021–22, respectively. Hence, the treatment 75% RDF + Azotobacter + PGPR + HA + SWE found better and can replace up to 25% RDF as comparable to conventional practice without compromising the crop yield.